Per-Oral Endoscopic Myotomy in Achalasia and Lung Abscess: A Case Report - Leite, Ana Bento; Maia, Mariana; Novo, Filipa (Brazilian Journal of Case Reports, 2025)
A lung abscess is defined as an infectious process with suppuration and cavitation. Lung abscess is more frequent in patients predisposed to aspiration due to achalasia. In the pre-antibiotic era, the mortality of patients with lung abscess was higher whereas today with the appropriate antibiotic therapy we can save these patients. The emergence of antibiotic-resistant strains is becoming a concern in such patients. Achalasia is an esophageal motility disorder characterized by loss of peristalsis and insufficient relaxation of the lower esophageal sphincter (LES). Per-oral endoscopic myotomy (POEM) should be considered the preferred treatment for achalasia because of its low invasiveness and high efficacy. The authors report a challenging case of a woman with achalasia, dysphagia, cough, weight loss who progressed to lung abscess caused by Pseudomonas aeruginosa and Klebsiella pneumoniae treated with antibiotics and POEM. This case report contributes to expanding knowledge on the management of lung abscess and achalasia, highlighting the importance of treatment with antibiotic therapy and POEM. Early treatment contributes to improving outcome and cutting socio-economic costs. Key facts to ameliorate to improve prognosis and length of hospital admission could be a swifter diagnosis and consensus on the antibiotic therapy.